2017
DOI: 10.1016/j.celrep.2017.11.082
|View full text |Cite
|
Sign up to set email alerts
|

The Arginine Methyltransferase PRMT6 Regulates DNA Methylation and Contributes to Global DNA Hypomethylation in Cancer

Abstract: SUMMARY DNA methylation plays crucial roles in chromatin structure and gene expression. Aberrant DNA methylation patterns, including global hypomethylation and regional hypermethylation, are associated with cancer and implicated in oncogenic events. How DNA methylation is regulated in developmental and cellular processes and dysregulated in cancer is poorly understood. Here, we show that PRMT6, a protein arginine methyltransferase responsible for asymmetric dimethylation of histone H3 arginine 2 (H3R2me2a), ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…Our present study finds PRMT6 to play a critical role in negatively regulating the maintenance of stemness feature of HCC cells. It is interesting to also note that, consistent with the study by Veland et al (2017), our pilot data also suggest that arginine methyltransferase activity of PRMT6 results in DNA hypomethylation in HCC cells, as evident by 5mc immunofluorescence staining. Specifically, global DNA hypomethylation was observed in cells overexpressing WT PRMT6 but not the catalytic inactive PRMT6 mutant (data not shown).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our present study finds PRMT6 to play a critical role in negatively regulating the maintenance of stemness feature of HCC cells. It is interesting to also note that, consistent with the study by Veland et al (2017), our pilot data also suggest that arginine methyltransferase activity of PRMT6 results in DNA hypomethylation in HCC cells, as evident by 5mc immunofluorescence staining. Specifically, global DNA hypomethylation was observed in cells overexpressing WT PRMT6 but not the catalytic inactive PRMT6 mutant (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…In the normal liver, PRMT6 promotes fasting-induced transcriptional activation of gluconeogenesis involving CRTC2 (Han et al, 2014). Earlier studies have suggested the regulatory function of PRMT6 in cellular proliferation, senescence, and cell cycle progression (Kleinschmidt et al, 2012;Phalke et al, 2012;Stein et al, 2012), while one very recent study reported on the role of PRMT6 in regulating DNA methylation and contributing to global DNA hypomethylation in cancers of the breast, prostate, colon, lung, nerve, and bone (Veland et al, 2017). Yet the disease-associated expression and function of PRMT6 in HCC have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The linked tandem Tudor domain (TTD) and PHD (Nady et al, 2011;Rajakumara et al, 2011;Rothbart et al, 2012), following the N-terminal ubiquitin-like domain (UBL) (Li et al, 2018), coordinately recognize a unique modification signature on the histone H3 tail (Arita et al, 2012;Cheng et al, 2013;Rothbart et al, 2013). Specifically, the PHD associates with the unmodified N terminus of H3 and is sensitive to methylation on arginine 2 (H3R2) (Cheng et al, 2013;Rajakumara et al, 2011;Veland et al, 2017), and this is enhanced by TTD recognition of di-or trimethylated lysine 9 on the same histone H3 tail (H3K9me2/me3) (Nady et al, 2011;Rothbart et al, 2012). The DNA binding SET and RING-associated (SRA) domain preferentially recognizes hemimethylated CpG dinucleotides generated during DNA replication (Avvakumov et al, 2008;Hashimoto et al, 2008), via a similar base-flipping mechanism used by DNMT1 (Song et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bisulfite sequencing was used to analysis the methylation of TRAF6 promoter region. The EZ DNA Methylation Kit (Zymo, Orange, CA, USA) was used to undertake bisulfite conversion, and the NEB PCR cloning kit (New England Biolabs, Ipswich, MA,USA), was used to clone PCR products and sequence individual clones . The primer sequences of bisulfite sequencing were: forward, 5′‐TGTTATAAAAGYGTAGTTTGGGATT‐3′; and reverse, 5′‐AATTCRAAAAAAATACCCCCTAAC‐3′.…”
Section: Methodsmentioning
confidence: 99%